Rancang Bangun Sistem Aplikasi Rehabilitasi (SIREHAB) dalam Pengelolaan dan Pengendalian Pecandu Narkotika dengan Menerapkan Metode Agile Software Development di Wilayah POLDA Jambi - Aminuddin, Fattachul Huda; Puad, Lailyn; Elzas, Elzas (Forum Kerjasama Pendidikan Tinggi, 2022)
Drug abuse is currently a very serious threat to the current generation. The current danger of drugs is so terrible that the government has to deal with drug abuse and drug addicts by means of rehabilitation. The National Police of the Republic of Indonesia, in particular the Directorate of Drugs and the Jambi Regional Police, based on the provisions of the applicable laws and regulations, regarding rehabilitation and narcotics addicts have an obligation to carry out a rehabilitation program. However, nationally, especially in Jambi Province, there is currently no reporting system on the management and control of narcotics addicts data online while based on 2021 data, the data on narcotics addicts is quite high, so it requires a system for monitoring the rehabilitation data for narcotics addicts to make it easier to monitor. its existence. In order to overcome the existing problems, the author wants to help and make it easier by designing and building an information system for the rehabilitation of narcotics addicts in the Jambi Regional Police area using the agile software development method. The purpose of building a system using this method is to assist and facilitate the management and control of narcotics addicts in the Jambi Regional Police by involving maximum involvement of stakeholders and related parties, especially the Narcotics Directorate and Jambi Regional Police so that the use of applications is more adaptive and can be developed more widely. more in responding to the challenges and changes that exist. The result of this research is that the system development is carried out using the agile software development method using six stages, namely meetings (meeting), planning (plan), design (develop), testing (test), and evaluation (evaluation). Based on the results of system testing carried out using black box testing, the system was as expected